Split 180° sequences - Freed, Denise E.; Scheven, Ulrich M.; Hürlimann, Martin D. (Diffusion Fundamentals, 2009)
In applications of NMR in inhomogeneous fields, sequences based on the Carr-Purcell-Meiboom-Gill (CPMG) sequence play a central role. The standard CPMG sequence consists of an initial 90° excitation pulse, followed by a long string of 180° refocusing pulses. This creates a series of echoes that decay with characteristic relaxation time T2eff. Here we present a modified sequence, the Split-180° sequence that specifically takes advantage of grossly inhomogeneous fields. In its simplest implementation, the 180° refocusing pulse of the CPMG sequence is split into two separate pulses. This sequence, which can be viewed as a modification of the CPMG sequence, simultaneously generates two types of signal that can be separately detected. One is a CPMG-like signal that decays with the expected relaxation time T2eff. In addition, a second type of signal builds up and approaches a steady-state. The amplitude of this dynamic equilibrium depends on the ratio of the longitudinal to the transverse relaxation times, T1/T2. We present experimental results and summarize the new theory that describes both signals in a unified manner.